Calcium Homeostasis and Sensitization in Pulmonary Arterial Smooth Muscle. (April 2014) - Jernigan, Nikki L.; Resta, Thomas C.
Abstract The pulmonary circulation is a low‐pressure, low‐resistance vascular bed with little to no resting tone under normal conditions. An increase in the [Ca2+]i in PASMCs is an important determinant of contraction, migration, and proliferation. Both Ca2+ influx through plasma membrane Ca2+ channels and Ca2+ release from the SR contribute to a rise in [Ca2+]i. Additionally important in the pulmonary circulation are several kinase‐mediated signaling pathways that act to increase the sensitivity of the contractile apparatus to [Ca2+]i. Similarly, cytoskeletal processes resulting in dynamic remodeling of the actin cytoskeleton can further contribute to contractility in the pulmonary circulation. In addition to endocrine, paracrine, and autocrine factors, alveolar hypoxia is an important stimulus for pulmonary vasoconstriction. However, prolonged hypoxia is a critical pathological stimulus associated with the development of pulmonary hypertension and cor pulmonale. In this review, we will discuss recent advances in our understanding of how Ca2+ homeostasis and sensitization regulate PASMC contractility under both physiological and pathophysiological conditions.